2006
DOI: 10.1111/j.1365-3156.2006.01739.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of artemether–lumefantrine for the treatment of uncomplicated falciparum malaria in northwest Cambodia

Abstract: Summaryobjective To determine the efficacy of artemether-lumefantrine malaria treatment, as an alternative to artesunate + mefloquine, which is becoming ineffective in some areas of the Thai-Cambodian border. With the per-protocol analysis, the cure rate was 71.1% in study AL2002, 86.5% in study AL2003 and 92.4% in study AM2003. All the data were PCR corrected. The artemether-lumefantrine cure rate was unexpectedly low in 2002, but it increased with food supplementation in 2003. There was a significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
4
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 18 publications
(21 reference statements)
2
114
4
4
Order By: Relevance
“…28 An increase in treatment success by 15% was observed in a study in Thailand when a fatty diet was coadministered with Coartem. 29 In this study, parents or guardians of the study participants were advised to administer treatment with a fatty diet, however, no information is available to what extent these recommendations were followed. Inadequate plasma concentrations of lumefantrine might therefore have contributed to the high rate of treatment failures.…”
Section: Discussionmentioning
confidence: 99%
“…28 An increase in treatment success by 15% was observed in a study in Thailand when a fatty diet was coadministered with Coartem. 29 In this study, parents or guardians of the study participants were advised to administer treatment with a fatty diet, however, no information is available to what extent these recommendations were followed. Inadequate plasma concentrations of lumefantrine might therefore have contributed to the high rate of treatment failures.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,20 To date, very few treatment failures had been documented with AL. [13][14][15] Some reported AL failures may have been due, as in our case, to incomplete drug administration rather than to parasite resistance. 13,15 Our study also showed that the fever clearance time was 44 ± 22.7 hours in patients treated with AL.…”
Section: Discussionmentioning
confidence: 93%
“…[13][14][15] Some reported AL failures may have been due, as in our case, to incomplete drug administration rather than to parasite resistance. 13,15 Our study also showed that the fever clearance time was 44 ± 22.7 hours in patients treated with AL. Although somewhat longer than that reported in previous AL studies, 16,18 it was shorter by 33 hours (a 57% reduction) than the fever clearance time on AP, which was 77 ± 28.0 hours (similar to that seen in other AP studies).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…36 Furthermore, the relation between resistant genotypes and most drug-resistant parasite phenotypes and clinical outcomes is not always straightforward. 37,38 Another difficulty is that the results from in-vitro assays after the use of ex-vivo techniques, such as SYBR-green-based protocols or isotope incorporation assays, are very difficult to compare between different sites because of differences in methods.…”
Section: Parasite Resistancementioning
confidence: 99%